2000
DOI: 10.1103/physrevc.62.014903
|View full text |Cite
|
Sign up to set email alerts
|

Charged particle production in the Pb+Pb system at 158GeV/cper nucleon

Abstract: Charged particle multiplicities from high multiplicity interactions of 158GeV/nucleon Pb ions with Pb target nuclei have been measured using nuclear emulsion chambers. The characteristics of these interactions have been compared to those of central interactions of 200 GeV/nucleon proton, O, and S beams on silver or bromine targets and those from simulations using the FRITIOF 7.02 and VENUS 4.12 Monte Carlo event generators. Multiplicities of Pb+Pb interactions in the central region are significantly lower than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…For η ′ > −1.5, the scaled pseudorapidity density actually grows in the peripheral data with respect to the more central data. This effect has already been observed for Au + Au collisions at √ s N N = 130 GeV [5] and for Pb + Pb collisions at 17 GeV [15], and is confirmed here for Au + Au at 19.6 and 200 GeV. This contradicts the suggestion, put forward in references [10,11], that the limiting curve for particle production in the fragmentation region is independent of centrality as well as of energy.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…For η ′ > −1.5, the scaled pseudorapidity density actually grows in the peripheral data with respect to the more central data. This effect has already been observed for Au + Au collisions at √ s N N = 130 GeV [5] and for Pb + Pb collisions at 17 GeV [15], and is confirmed here for Au + Au at 19.6 and 200 GeV. This contradicts the suggestion, put forward in references [10,11], that the limiting curve for particle production in the fragmentation region is independent of centrality as well as of energy.…”
contrasting
confidence: 47%
“…It should be noted that the very peripheral limit of a Au + Au collision is not an N + N collision, but rather an N + N collision with two large excited nuclear remnants, one of which is at y ′ = 0. The increased particle production near y ± y beam = 0 due to the nuclear remnants has been studied in p + A collisions [16] and for lower energy Pb+Pb collisions [15]. The narrowing of the overall distribution may be due to dynamical effects, such as baryon stopping [17], or kinematic effects, such as a shift in η ′ (for fixed y ′ ) due to the particle mix (p/π ratio) changing with centrality.…”
mentioning
confidence: 99%
“…Limiting fragmentation has been observed in a variety of hadronic collisions [68][69][70], including nucleus-nucleus interactions [26][27][28][29][30]. It was observed that in the region of limiting fragmentation the particle density increases linearly with the rapidity before reaching a plateau.…”
Section: Limiting Fragmentationmentioning
confidence: 99%
“…Another convenient and useful parameter to calculate the multiplicity per participating nucleon is given as M = n / W. Here, the wounded nucleon W contains the all quantities of geometrical effects such as nuclear radius, density and impact parameter. It is believed that M depends only on the interaction dynamics of the collision and not on the impact parameter (b) [15][16]. From the purely geometrical aspects, the number of wounded nucleons or participating nucleons from the projectile and target nuclei, and the nuclear interactions are given in terms of the interaction cross-section as…”
Section: Wounded Nucleon Modelmentioning
confidence: 99%